1996
DOI: 10.1074/jbc.271.30.17920
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Structure and Function of a New Mitogen-activated Protein Kinase (p38β)

Abstract: Mitogen-activated protein (MAP) kinase cascades represent one of the major signal systems used by eukaryotic cells to transduce extracellular signals into cellular responses. Four MAP kinase subgroups have been identified in humans: ERK, JNK (SAPK), ERK5 (BMK), and p38. Here we characterize a new MAP kinase, p38␤. p38␤ is a 372-amino acid protein most closely related to p38. It contains a TGY dual phosphorylation site, which is required for its kinase activity. Like p38, p38␤ is activated by proinflammatory cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
582
3
11

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 709 publications
(609 citation statements)
references
References 47 publications
13
582
3
11
Order By: Relevance
“…Although the other three p38 group members have been cloned for quite some time now, little is known regarding their activation. Despite research that has shown that all four p38 group members display similar activation profiles [5,8,24,25], differences have been observed in the kinetics and level of activation of these isoforms. Furthermore, the activation of p38 isoforms can be specifically controlled through different regulators and coactivated by various combinations of upstream regulators [24,26].…”
Section: Properties Of P38 Map Kinase Membersmentioning
confidence: 91%
See 1 more Smart Citation
“…Although the other three p38 group members have been cloned for quite some time now, little is known regarding their activation. Despite research that has shown that all four p38 group members display similar activation profiles [5,8,24,25], differences have been observed in the kinetics and level of activation of these isoforms. Furthermore, the activation of p38 isoforms can be specifically controlled through different regulators and coactivated by various combinations of upstream regulators [24,26].…”
Section: Properties Of P38 Map Kinase Membersmentioning
confidence: 91%
“…p38 cDNA was also cloned as a molecule that binds puridinyl imidazole derivatives which are known to inhibit biosynthesis of inflammatory cytokines such as interleukin-1 (IL-1) and tumor-necrosis factor (TNF) in LPS stimulated monocytes [4]. To date, four splice variants of the p38 family have been identified: p38α, p38β [5], p38γ (ERK6, SAPK3) [6,7], and p38δ (SAPK4) [8,9]. Of these, p38 and p38β are ubiquitously expressed while p38γ and p38δ are differentially expressed depending on tissue type.…”
Section: Properties Of P38 Map Kinase Membersmentioning
confidence: 99%
“…The constitutively active MKK3-expressing construct has been described elsewhere (Han et al, 1996;Jiang et al, 1996) and mock control was prepared using the empty vector (pcDNA3). For reporter-gene assays 1 mg of empty vector or reporter-gene vector encoding the FoxM1 promoter in front of the luciferase gene (Korver et al, 1997;Laoukili et al, 2005) were transfected into the respective cell lines or cotransfected with the constitutively active MKK3 expression construct using the JetPrime reagent (PeqLab, Erlangen, Germany) at a 1:1 ratio.…”
Section: Western Blotting and Immunoprecipitationmentioning
confidence: 99%
“…The second subtype JNK/SAPKs, are characterised by the sequence TPY in the activation domain Kallunki et al, 1994;Kyriakis et al, 1994), while the third, p38/ RK (p38, Han et al, 1994;CSBP, Lee et al, 1994;RK, Rouse et al, 1994;p40, Freshney et al, 1994;Mxi2, Zervos et al, 1995, referred to hereafter as p38/RK), has the motif TGY in this position. More recently, other variants of p38/RK, called SAPK3 (Mertens et al, 1996) and p38b (Jiang et al, 1996) have been identi®ed. These subtypes may be activated in parallel but to distinct extents by di erent stimuli (reviewed in Cooper, 1994;Cano and Mahadevan, 1995;Seger and Krebs, 1995).…”
Section: Introductionmentioning
confidence: 99%